Infeksi Trichophyton rubrum Terhadap Personal Hygiene Nelayan dan Pengolah Ikan Rumahan di Kota Bengkulu The incidence of Trichophyton rubrum infection related to personal hygiene between fishermen and home-based fish processors in Bengkulu City. - Gabriella Christie Susanti; Besly Sinuhaji; Dessy Triana (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
Purpose: This study aimed to compare the incidence of Trichophyton rubrum fungal infections related to personal hygiene between fishers and home-based fish processors in coastal communities in Kampung Nelayan, Sumber Jaya District, Bengkulu City. Method: This observational-analytic cross-sectional study took the consecutive sampling of 124 fishers and domestic fish processors in the research site. Data collection used questionnaires to obtain demographic characteristics and personal hygiene data. This study used a 10-20% KOH examination to diagnose dermatophytosis and fungal culture on Sabouraud Dextrose Agar to identify Trichophyton rubrum. Results: The highest incidence of dermatophytosis was tinea pedis (50%). Fishers and home fish processors in the research site had poor personal hygiene (100%) and 8.9% were infected with Trichophyton rubrum. Conclusions: There is no difference in Trichophyton rubrum fungal infections between fishers and home fish processors.